Moderate Iodine Deficiency Is Common in Pregnancy but Does Not Alter Maternal and Neonatal Thyroid Function Tests - Schiller, Tal; Agmon, Arnon; Ostrovsky, Viviana; Shefer, Gabi; Knobler, Hilla; Zornitzki, Taiba (Frontiers in Endocrinology, 2020)
Introduction An Israeli national survey found that 85% of pregnant women had urinary iodine content (UIC) levels below the adequacy range (<150 µg/L). Widespread desalinated water usage and no national fortification plan are possible causes. Studies assessing relationships between iodine status and maternal and neonatal thyroid function provided varying results. Our aims were to determine whether iodine deficiency was associated with altered maternal or neonatal thyroid function and the factors leading to iodine deficiency. Methods A cross-sectional study including 100 healthy women without prior thyroid disease, in their first trimester of a singleton pregnancy, were recruited from an HMO clinic in central Israel. The women were followed from their first trimester. All women completed a 24-hour dietary recall and life habits questionnaires. We tested for UIC, maternal and neonatal thyroid function, maternal autoantibodies, and neonatal outcomes. Results Median UIC in our cohort was 49 µg/L [25%-75% interquartile range (IQR) 16-91.5 µg/L], with 84% below adequacy range. No correlation was found between iodine deficiency and maternal or neonatal thyroid function which remained within normal ranges. Antibody status did not differ, but thyroglobulin levels were significantly higher in iodine insufficient subjects. UIC was higher in women consuming an iodine-containing supplement. There was no association between UIC and dietary iodine content or water source. Conclusions Moderate iodine deficiency is common in our healthy pregnant women population. Our data imply that moderate iodine deficiency in pregnancy seems sufficient to maintain normal maternal and neonatal thyroid function.